Branding Plan for Arctic Well Spring Water: Establishing a Premium Brand in China - Lesonen, Essi (Oulun ammattikorkeakoulu, 2015)
The Chinese middle class has been growing at a fast pace during the past years and they have more purchasing power than ever. The growing middle class is also concerned about their health and safety and they are willing to spend money on premium international water. The idea for this thesis came from a group of people in Finland and China who are interested in exporting spring water from the Finnish Lapland to China. The reason for choosing China was the enormity and potential of the market. The thesis serves as a branding guideline for the founders of Arctic Well and helps them to determine what things need to be considered before establishing the company. Creating a strong brand right from the start is important when entering such a vast market as a small business. The thesis is purely functional and information and data was gathered from different sources as well as from the author’s own experiences while living in China. The outcome of this thesis is a guide for Arctic Well on how to start building a brand before it has been established and during the early growth stages. It also explains about the target market and gives advice about positioning and differentiating themselves in the market.